Saturation mutagenesis on Arg244 of the tryptophan C4-prenyltransferase FgaPT2 leads to enhanced catalytic ability and different preferences for tryptophan-containing cyclic dipeptides - Fan, Aili; Li, Shu-Ming (Applied microbiology and biotechnology, 2016)
FgaPT2 from Aspergillus fumigatus catalyzes a Friedel–Crafts alkylation at C-4 of l -tryptophan and is involved in the biosynthesis of the ergot alkaloids fumigaclavines. Several tryptophan-containing cyclic dipeptides had also been prenylated by FgaPT2, but the turnover rate ( k cat ) was low. Here, we report the generation of FgaPT2 mutants by saturation mutagenesis at the amino acid residue Arg244 to improve its catalytic efficiency toward cyclic dipeptides. Thirteen mutated enzymes demonstrated up to 76-fold higher turnover number toward seven cyclic dipeptides than the non-mutated FgaPT2. More importantly, the mutated enzymes exhibited different preferences toward these substrates. This study provides a convenient approach for creation of new biocatalysts for production of C4 -prenylated cyclic dipeptides.